Properties of Heterologous anti-Ebola Immunoglobulin after Long Storage - S. A. Melnikov; I. V. Borisevich; E. V. Rozhdestvensky; V. B. Pantyukhov; N. K. Chernikova; E. V. Gordeev; S. A. Nimirskaya; A. L. Khmelev; S. I. Syromyatnikova; I. V. Shatokhina; T. M. Plekhanova; G. D. Timankova; et al. (Биопрепараты: Профилактика, диагностика, лечение, 2020)
Ebola outbreak in eastern parts of the Democratic Republic of the Congo in 2018–2020 proved that the virus remains highly hazardous for humans, and the outbreak in West Africa in 2014–2016, which was the largest Ebola outbreak in history, showed that it could be imported to other continents, including Russia. In 1993 the Federal State Budgetary Institution “48th Central Scientific Research Institute” of the Russian Ministry of Defence developed a specific equine immunoglobulin for emergency prophylaxis of Ebola in risk groups. The evaluation and improvement of the product’s properties is an important area in the development of biological defence technologies.The aim of the study was to examine the properties of the equine anti-Ebola immunoglobulin which had been stored for a long time at 2–8 °C.Materials and methods: the authors studied batches of heterologous anti-Ebola immunoglobulin that had been stored for 17–22 years. The properties of the product were evaluated according to the requirements of the State Pharmacopoeia of the Russian Federation, 14th ed. (Ph. Rus. 14 ed.). The specific activity of the product was determined in a plaque reduction neutralisation test using Ebola virus and African green monkey kidney cells (GMK-AH-1(D)). Immunoglobulin molecular parameters were determined by size-exclusion high-performance liquid chromatography using the test methods described in the European Pharmacopoeia 9.6 and Ph. Rus. 14 ed.Results: the storage of anti-Ebola immunoglobulin for 17–22 years at 2–8 °C resulted in a four-fold reduction of the level of virus-neutralising antibodies against Ebola, decrease in the proportion of monomers from 98 to 74–90%, increase in the proportion of dimers and polymers, and formation of immunoglobulin molecules’ fragments. Signs of toxicity for mice were observed in one of the three product batches. Conclusions: the obtained results suggest the need to perform more studies to test the quality of antiEbola immunoglobulin batches that were stored for shorter periods of time in order to assess the stability of their initial characteristics.